2020
DOI: 10.3201/eid2610.202449
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA Load in Mildly Symptomatic and Asymptomatic Children with COVID-19, Seoul, South Korea

Abstract: Along with positive SARS-CoV-2 RNA in nasopharyngeal swabs, viral RNA was detectable at high concentration for >3 weeks in fecal samples from 12 mildly symptomatic and asymptomatic children with COVID-19 in Seoul, South Korea. Saliva also tested positive during the early phase of infection. If proven infectious, feces and saliva could serve as transmission sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
199
3
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(227 citation statements)
references
References 8 publications
20
199
3
5
Order By: Relevance
“…In 9 patients with confirmed SARS-CoV-2 infections one of the patients was positive for viral RNA in urine [150]. This observation is supported by observations among 12 SARS-CoV-2 positive children with 2 of them positive for viral RNA in urine (17%) [119]. Importantly, infectious virus could be detected from urine in one COVD-19 patient [151].…”
Section: Urinary Tractsupporting
confidence: 58%
See 1 more Smart Citation
“…In 9 patients with confirmed SARS-CoV-2 infections one of the patients was positive for viral RNA in urine [150]. This observation is supported by observations among 12 SARS-CoV-2 positive children with 2 of them positive for viral RNA in urine (17%) [119]. Importantly, infectious virus could be detected from urine in one COVD-19 patient [151].…”
Section: Urinary Tractsupporting
confidence: 58%
“…In contrast, one study described the successful isolation of virus by cell culture from 2 out of 3 patients [118]. Of note, another study showed higher viral RNA loads in fecal samples of mildly symptomatic or asymptomatic children compared to nasopharyngeal swabs [119]. These results indicate the possibility of fecal-oral transmission or fecal-respiratory transmission through aerosolized feces.…”
Section: Gastrointestinal Tract / Stoolmentioning
confidence: 98%
“…SARS-CoV-2 viral load is highest at the onset of illness and wanes over time regardless of age or illness severity, as the authors themselves argue (Figure 2, panel C) ( 3 , 4 ). While the authors state that viral loads in children were high, they were not higher than levels reported by others in either adults or children at similar time points after onset of symptoms ( 5 , 6 , 7 ). Inferring anything about the infectivity of the COVID-19 positive children is speculative.…”
contrasting
confidence: 52%
“…Questions relating to the role of viral carriage in the pediatric population can be addressed using these samples. Case reports and recent research studies suggests that asymptomatic children carry high viral loads despite lack of symptoms [4][5][6]. In adults, severe infection is not necessarily associated with a signi cant increase in viral loads by nasopharyngeal swab [7], and asymptomatic individuals appear to have equal viral loads as symptomatic individuals [8].…”
Section: Inform Pediatric Contribution To Viral Transmissionmentioning
confidence: 99%